2001
DOI: 10.1002/jnr.10044
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate carboxylation in neurons

Abstract: Carboxylation of pyruvate in the brain was for many years thought to occur only in glia, an assumption that formed much of the basis for the concept of the glutamine cycle. It was shown recently, however, that carboxylation of pyruvate to malate occurs in neurons and that it supports formation of transmitter glutamate. The role of pyruvate carboxylation in neurons is to ensure tricarboxylic acid cycle activity by compensating for losses of alpha-ketoglutarate that occur through release of transmitter glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 74 publications
(78 reference statements)
1
33
0
3
Order By: Relevance
“…115 Studies in rats injected with 13 C-labelled lactate (believed to be a predominantly neuronal substrate) showed that lactate was metabolized in a compartment without measurable pyruvate carboxylation. 116,117 In analogous experiments in mice, however, Hassel and colleagues reported neuronal carboxylation of pyruvate generated from labelled lactate, 115 which has been suggested to be mediated through neuronal malic enzyme. In contrast to the almost exclusive localization of cME in astrocytes, mitochondrial ME has been found in both astrocytes and neurons as well as synaptosomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…115 Studies in rats injected with 13 C-labelled lactate (believed to be a predominantly neuronal substrate) showed that lactate was metabolized in a compartment without measurable pyruvate carboxylation. 116,117 In analogous experiments in mice, however, Hassel and colleagues reported neuronal carboxylation of pyruvate generated from labelled lactate, 115 which has been suggested to be mediated through neuronal malic enzyme. In contrast to the almost exclusive localization of cME in astrocytes, mitochondrial ME has been found in both astrocytes and neurons as well as synaptosomes.…”
mentioning
confidence: 99%
“…In contrast to the almost exclusive localization of cME in astrocytes, mitochondrial ME has been found in both astrocytes and neurons as well as synaptosomes. 31,64,114,118-121 ME has a maximal carboxylating activity in whole brain that is 30-60% of -ketoglutarate dehydrogenase (-KGDH, a rate-limiting enzyme of the TCA cycle 115 ). As it provides fourcarbon sources to ensure normal glucose oxidation (entry of acetyl-CoA into the TCA cycle), neuronal ME may become an important component in situations of energy deficit or during neuronal activity/stimulation.…”
mentioning
confidence: 99%
“…ME2 is a genome-coded mitochondrial enzyme that converts malate to pyruvate. Recessively inherited ME2 deficiency could indirectly decrease neuronal synthesis of the neurotransmitter γ -aminobutyric acid (GABA), in that it supplies pyruvate for GABA synthesis (14). Compelling lines of evidence show that an impaired GABAergic inhibition increases neuronal excitability and may contribute to epileptogenesis (15,16).…”
mentioning
confidence: 99%
“…Algunos de estos episodios se caracterizaron por una disminución brusca y reversible en los niveles de piruvato que podría sugerir una intensa carboxilación del piruvato para sintetizar glutamato a través de la ruta anaplerótica del ciclo de Krebs 13 . En la Figura 5 se observa un ejemplo de este comportamiento observado en un paciente con TCE y monitorizado mediante microdiálisis cerebral.…”
Section: íNdice Lpunclassified